Modification of the existing maximum residue levels for flonicamid in various crops - European Food Safety Authority (EFSA); Giulia Bellisai; Giovanni Bernasconi; Luis Carrasco Cabrera; Irene Castellan; Monica delAguila; Lucien Ferreira; German Giner Santonja; Luna Greco; Samira Jarrah; Renata Leuschner; Andrea Mioč; et al. (EFSA Journal, 2024)
Abstract In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant ISK Biosciences Europe N.V. submitted two requests to the competent national authority in Finland and Belgium, respectively, to modify the existing maximum residue levels (MRLs) for the active substance flonicamid in potatoes and in various crops. The data submitted in support of the requests were found to be sufficient to derive MRL proposals for potatoes, lettuces and salad plants, spinaches and similar leaves, beans (without pods), cardoons, celeries, Florence fennels and rhubarbs. Adequate analytical methods for enforcement are available to control the residues according to the residue definition as of the sum of flonicamid, TFNA and TFNG, expressed as flonicamid in the plant matrices under consideration at the validated limit of quantification (LOQ) of 0.01 mg/kg for each compound. Based on the risk assessment results, EFSA concluded that the short‐term and long‐term intake of residues resulting from the uses of flonicamid according to the reported agricultural practices is unlikely to present a risk to consumer health.